Application of Wound Care Using 0.9% NaCl Solution in Patients with Type II Diabetic Ulcers in the Wijaya Kusuma Bawah Ward of Kardinah Regional General Hospital, Tegal City - Tajkiatul Musaropah, Hilma; Fadila, Erida (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Diabetic ulcers are a condition that occurs in patients with diabetes mellitus due to nerve abnormalities and peripheral artery disorders, leading to infection in wounds and tissue damage in the skin of the feet (Roza et al., 2015). The objective of this scientific study is to apply wound care and evaluate the effectiveness of wound care using 0.9% NaCl in patients with Type II diabetic ulcers. Method: The method used in this scientific study is a case study. The subject of this study is one patient with Type II Diabetic Ulcer who is undergoing treatment in the Wijaya Kusuma Bawah ward of Kardinah General Hospital in Tegal City. Data collection was conducted using interview techniques, observation, and documentation. Result: Nursing care was provided for three consecutive days. During the assessment, it was found that the patient experienced pain in the left foot wound, which had been present since September but had not healed and had worsened. The wound was dirty, smelly, and oozing pus. The intervention provided was wound care using EBN with 0.9% NaCl, implemented over three consecutive days. By the third day, the evaluation showed that skin integrity had been restored. Conclusion: The author concludes that wound care using 0.9% NaCl is effective, as there was an improvement in the wound condition.